¿Cómo se ajustan los costos del trabajo en distintos periodos económicos? (México urbano : 1989-1995) - Parker, Susan Wendy; Pacheco Gómez Muñoz, Edith (El Colegio de México A.C., 1996)
In recent years studies about labour market dynamics have emphasized great changes such as: the rise of self-employment as opposed to the incapability to generate salaried-labour sources; the increase of small economic establishments, and the increase of female employment. Experts have also paid attention, although to a lesser degree, to the remunerative conditions of workers; moreover, there are few studies about the characteristics of labour market exits and about the workday. This paper explores these last lines of research, while anylizing the possible adjustments in labour costs, during a period of time where different economic situations are contemplated.